Peranan Aplikasi SiApik dalam Membantu Penyusunan Laporan Keuangan UMKM: Studi Kasus Warung Wak Waw - Thresia Nainggolan, Yohanna; Bahtiar; Febriyanti, Nabilah; Sari, Lela; Shari, Meysi Maulida (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study investigates the role of the SiApik application in supporting the preparation of financial reports for Micro, Small, and Medium Enterprises (MSMEs), using Warung Wak Waw in Tarakan City as a case study. MSMEs frequently encounter obstacles in recording and presenting systematic financial reports in accordance with accounting standards. The SiApik application offers a practical digital solution for transaction recording, income statement generation, and financial performance evaluation. Employing a qualitative approach with case study methods, including observation and interviews, the findings demonstrate that the use of SiApik enhances both the accuracy and efficiency of financial recording, while also strengthening the basis for more precise business decision-making. These results suggest that adopting technology in financial management constitutes an effective strategy to advance MSME development in the Tarakan region.